Capital flight and External debt in Nigeria - Ajayi Ibi S.; African Economic Research Consortium (Nairobi : African Economic Research Consortium, 1995)
The paper addresses general issues on capital flight as it's link with growth, reduces the rate capital formation which adversely affects the country's current and future prospects.
Includes bibliography
gp. 23/01/2019
loan
Keywords: Capital flight; External debts; Economic conditions; Nigeria